Efficacy of Endovascular Therapy in Acute Ischemic Stroke Depends on Age and Clinical Severity. Issue 7 (July 2018) - Le Bouc, Raphaël; Clarençon, Frédéric; Meseguer, Elena; Lapergue, Bertrand; Consoli, Arturo; Turc, Guillaume; Naggara, Olivier; Duong, Duc Long; Servan, Jerome; Reiner, Peggy; Labeyrie, Marc Antoine; Fisselier, Mathieu; et al.
Abstract : Background and Purpose—: Efficacy of endovascular treatment (EVT) for ischemic stroke because of large vessel occlusion may depend on patients' age and stroke severity; we, therefore, developed a prognosis score based on these variables and examined whether EVT efficacy differs between patients with good, intermediate, or poor prognostic score. Methods—: A total of 4079 patients with an acute ischemic stroke were identified from the Paris Stroke Consortium registry. We developed the stroke checkerboard (SC) score (SC score=1 point per decade ≥50 years of age and 2 points per 5 points on the National Institutes of Health Stroke Scale) to predict spontaneous outcome. The primary outcome was the adjusted common odds ratio for an improvement in the modified Rankin Scale at 90 days after EVT, in patients with low, intermediate, or high SC scores. To rule out potential selection biases, a nested case-control analysis, with individual matching for all major prognostic factors, was also performed, to compare patients with large vessel occlusion in the anterior circulation treated or not with EVT. Results—: In patients untreated with EVT, SC scores <8 were predictive of good outcomes (modified Rankin Scale score, 0–2; area under the curve, 0.87), whereas SC scores >12 were predictive of poor outcomes (modified Rankin Scale score, 4–6; area under the curve, 0.88). In the overall population, there was an interaction between EVT and prognosis group ( P <0.001). EVT was associated with improved outcome in patients with SC scores >12 (common odds ratio, 1.70; 95% confidence interval, 1.13–2.56) and SC scores 8 to 12 (odds ratio, 1.37; 95% confidence interval, 1.11–1.69) but not in patients with SC scores <8 (odds ratio, 0.72; 95% confidence interval, 0.56–0.93). Similar results were obtained in the case-control analysis among 449 patients treated with EVT and 449 matched patients untreated with EVT. Conclusions—: In patients stratified with the SC score, EVT was associated with improved functional outcome in older and more severe patients but not in younger and less severe patients. Abstract : Supplemental Digital Content is available in the text.